A Dança e as Leis do Movimento: uma proposta para o ensino de Física - Pantano Filho, Rubens (2024)
In the context of reflections on the teaching of Physics in High School (HS), this dissertation contemplates an educational product that consists of a set of proposals for teaching concepts related to basic Mechanics and the laws associated with them, using Art – particularly Dance – as a support point and motivational element. Thus, we seek to bring together these two areas of knowledge inserted in two fields of knowledge that – apparently – do not present intersections or even approximations. In this way, Science – Physics in particular – is also treated as an element of the broad spectrum of culture, just as other human activities are traditionally considered as such: literature, music, fashion, gastronomy, religion, sport, customs, politics, among others. The work developed presents the studies of João Zanetic as its theoretical reference, from the University of São Paulo (Brazil), Luís Paulo Piassi, also from the University of São Paulo (Brazil), Glen Aikenhead, from the University of Saskatchewan (Canada) and Maria Eduarda Vaz Moniz dos Santos, from the University of Lisbon (Portugal). The proposals if this study include videos of folk, classical, ballroom, contemporary and/or competition dances, as well as images of dancers at specific moments of their performances, all appropriate as elements for discussing some themes of Classical Mechanics. Thus, we develop activities that bring Physics and Dance together and involve the typical physical concepts inherent to the study of movements: reference, displacement, speed, acceleration, force, energy and its conservation, torque and balance. The educational product was applied to three first-year classes of three Technical Courses (Electroelectronics, Computing and Mechanics) Integrated into High School at a federal educational institution in the city of Bragança Paulista, SP. In the activities carried out throughout an academic year, it is possible to observe a good motivation of the students involved in dealing with the topics. Furthermore, the respective evaluation processes also demonstrated an appropriate understanding of the concepts worked on in the application of the product.